A Comparative Analysis of Crank-Nicolson Scheme between Finite Volume Method and Finite Dierence Method for Pricing European Option - Heyath Sajib, Mohammad Abul; Hossain, A B M Shahadat; Sudha, Sushoma (GANIT: Journal of Bangladesh Mathematical Society, 2022)
The value of European option (call and put) is evaluated in this work by discretizing the Black-Scholes (BS) equation using two numerical procedures: _nite volume method (FVM) and _nite di_erence method (FDM). Both methods can be classi_ed into three schemes: explicit, implicit, and Crank-Nicolson. The primary goal of this work is to compare the results of Crank-Nicolson FVM (CNFVM) and Crank-Nicolson FDM (CNFDM), considering the BS model as a benchmark. From the comparison, we conclude that CNFVM gives more accurate approximations than CNFDM. GANIT J. Bangladesh Math. Soc. 42.2 (2022) 1- 13